(untitled) (Journal of Information Technologies in Education (ITE), 2014)
The essence of pedagogical diagnostics and its functions in the learning process is considered. The use of pedagogical diagnostics in distance learning to help the student in choosing the expedient for him variant of independent work that contributes to personal orientation of the educational process is analysed. Structure of the pedagogical diagnostics system is proposed,requirements to the system, the stages and procedure of its design are discussed.